Verbal Bullying In Students at School - Maryati, Maryati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Bullying is a social phenomenon that has become a serious concern in various communities, especially in educational settings. One form of bullying that often occurs in schools is verbal bullying, where learners are victimized by harsh words, insults, or threats that can be emotionally detrimental. Verbal bullying is not only damaging to students' psychological well-being, but can also have a long-term impact on their social and academic development. Based on recent data and research, verbal bullying has become an increasingly troubling problem in many schools. This article aims to shed a comprehensive light on verbal bullying of learners in school settings. Through a better understanding of this phenomenon, it is hoped that we can develop more effective prevention efforts and create a safe and supportive educational environment for all learners. In doing so, it is hoped that this article can be a useful source of information and promote awareness of the importance of combating verbal bullying in schools.